Tax compliance costs: A review of cost burdens and cost structures - Sebastian Eichfelder; François Vaillancourt (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
Our paper provides a comprehensive report of empirical research on tax compliance costs. Compared to previous reviews, our focus is on average costs for sub-groups (individual taxpayers, small businesses, large businesses) and the composition of the cost burden with regards to different cost components (in-house time effort, external adviser costs, other monetary expenses), different taxes (e.g. income tax, value added tax) and different activities like tax accounting and tax planning. In addition, we give a short review of the most important compliance cost drivers and discuss the underlying causes of tax complexity and compliance costs.
Keywords: H21; H24; H25; 330; tax compliance costs; cost structures; cost burdens; cost drivers